MODELING OF A SPRAY ASSISTED NATURAL DRAFT COOLING TOWER - Kaunde, O. K. (Tanzania Journal of Engineering and Technology, 2018)
Cooling towers are one of the largest heat and mass transfer devices that are in common use. A novel type of cooling tower has been proposed in which air flow rate into the tower is drawn by ejector action of sprays instead of fans as is done in conventional mechanical forced or induced draft cooling towers. This novel design offers the potential of saving the energy cost for driving the fan. The paper presents mathematical models for momentum transfer which is the driving force causing the entrainment of air. Also the heat transfer model for co-current flow of liquid and gas in the tower has been presented. The liquid to gas ratio tend to decrease as liquid rate increases. The ratio attained in the experimental laboratory tower was 3.3, correspondingly the Momentum transfer efficiency for the tower was 60% and was the highest. Experiments for cooling water initially at 45 o C to final water temperature 27 o C showed that the cooling tower efficiency was 54% and number of transfer unit 0.8.